Role of intercultural education in the conservation and sustainable management of natural resources, with emphasis on food systems - Rosado-May, Francisco Javier (2018)
In Mexico, and other areas of Latin America, around to 80 % of the country’s natural resources (NR) are in the territories, hands, and the minds, of indigenous communities. Most of the research regarding management of NR in indigenous areas, link their culture to the sustainable use of NR. Unfortunately, the culture, which includes sophisticated systems of learning and constructing knowledge, is not taught in conventional schools, much less at university level. In fact, research shows that indigenous people lose confidence in their traditional ways of constructing knowledge and have strong difficulties acquiring the new system taught in schools. Thus, indigenous knowledge that carries out centuries of experimentation is being lost. This paper discusses a model, called intercultural education in Mexico, for higher education. The working definition for intercultural education, coined at the Intercultural Maya University of Quintana Roo (UIMQRoo), is: intercultural education is a process that takes place in a safe environment in which different systems of learning and constructing knowledge coexist, creating new avenues to innovate systems of teaching-learning-and constructing knowledge, using the best of indigenous and modern systems. Examples from agroecology and education, both academic programs at UIMQRoo, are presented and discussed to illustrate successful results of intercultural education. Access to education and food sovereignty, according to the cultural bases of indigenous people, are important not only from the human rights point of view but also for the social fabric and overall sustainability of a country, especially in a multicultural setting.